Heir to the Crescent Moon - Abdur-Rahman, Sufiya (Book collections on Project MUSE., 2021)
"From age five, Sufiya Abdur-Rahman, the daughter of two Black Power-era converts to Islam, feels drawn to the faith even as her father, a devoted Muslim, introduces her to and, at the same time, distances her from it. He and her mother abandoned their Harlem mosque before she was born and divorced when she was twelve. Forced apart from her father--her portal into Islam--she yearns to reconnect with the religion and, through it, him. In Heir to the Crescent Moon, Abdur-Rahman's longing to comprehend her father's complicated relationship with Islam leads her first to recount her own history with it. Later, as she seeks to discover what both pulled her father to and pushed him from the mosque and her mother, Abdur-Rahman delves into the past. She journeys from the Christian righteousness of Adam Clayton Powell Jr.'s 1950s Harlem, through the Malcolm X-inspired college activism of the late 1960s, to the unfulfilled potential of the early-'70s' black American Muslim movement. When a painful reminder of the reason for her father's inconsistent ties to his former mosque appears to threaten his life, Abdur-Rahman's search nearly ends. She's forced to come to terms with her Muslim identity, and learns how events from generations past can reverberate through the present. Told, at times, with lighthearted humor or heartbreaking candor, Abdur-Rahman's story of adolescent Arabic lessons, fasting, and Muslim mosque, funeral, and eid services speaks to the challenges of bridging generational and cultural divides and what it takes to maintain family amidst personal and societal upheaval. Writing with quiet beauty but intellectual force about identity, community, violence, hope, despair, and faith, Abdur-Rahman weaves a vital tale about a family: black, Muslim, and distinctly American"--